Desecrate the territories - Vidal, Raúl (2025)
The present rests on ruins, which the Angel of History looks at in the midst of the storm of progress. Does a psychoanalysispropose artifices (the force of an image, a play on words, the scales of the act) that contradict the real unbridled of the outside lockdown suffered by migrant bodies?